Web Content Mining Framework for Discovering University Formations’ Compatibility with the Market Needs - Camelia Elena CIOLAC; Florica LUBAN; Răzvan Cătălin DOBREA (Revista de Management Comparat International)
This paper aims to provide a decision tool for both academia and business in order to better reach convergence between the qualifications offered and demanded for fresh graduates. The study discovers the IT market’s request of capabilities by applying web-mining techniques on the main Romanian job web portals. Then, the study gathers information about the specific qualifications provided to students in both undergraduate and master computer science programs in five representative Romanian universities. Based on these findings, we propose a model to evaluate the degree of alignment of these two sets. The model is useful for all stakeholders: universities, companies including small and medium size enterprises, as a tool of career planning and it can be adapted to assess the best mobility program for students, as further discussed in the paper.